UPAYA MENINGKATKAN KUALITAS PRODUK PADA AULIYA MEUBEL SINTANG - Magdalena, Lin (Universitas Kapuas Sintang, 2024)
The research aims to find out and describe efforts to improve product quality at Auliya MeubelSintang. The scope of this research is: 1. Quality of Raw Materials 2. Human Resources 3. Facilities andInfrastructure 4. Capital. This type of research is descriptive qualitative research. The research subjects are:1. Owner of Auliya Meubel Sintang 2. Employees of Auliya Meubel Sintang. 3. Consumers of AuliyaMeubel Sintang. Data collection techniques: interviews, observation and documents. Data collection toolsare interview guidelines, observation guidelines, and documentation tools. Data analysis steps: datareduction, data presentation, and drawing conclusions. Research results: Auliya Meubel improves thequality of raw materials for furniture by using solid wood, also providing other materials such as HPL,metal, plywood, multiplex, plastic, glass and other more affordable alternative materials. Has 2 (two)employees who have the ability to make furniture. Improve employee skills by encouraging them to learnvia YouTube or learn directly from experienced furniture craftsmen. Motivate employees to increaseproductivity by providing overtime pay and THR. Has furniture production machines by adding newmachines to improve the quality of furniture such as router machines and compressor machines. Increasebusiness capital by borrowing from the bank (KUR)